Ekosufisme Sebagai Upaya Menjaga Kelestarian Lingkungan Melalui ProKlim (Program Kampung Iklim) - Pra Fitri, Dianing (Spiritualita, 2025)
Climate change is an important issue that must be addressed collectively. In order to overcome the problem of climate change that is occurring, every small group in society has an effort to deal with climate change through ProKlim activities. The aim of this research is to describe the implementation and role of ecosufism in preserving the environment through ProKlim in Kudus Regency. This research uses descriptive qualitative methods through observation, interviews and literature studies carried out directly during the research process. Findings from research related to ProKlim activities can be expressed in terms of ecosufism through the concept of eco-sufism using the hierarchy of takhalli, tahalli, and tajalli as methods used to preserve nature. This research shows that the eco-Sufism approach is able to build spiritual awareness and remind us of the importance of preserving the environment.